Financial Supervision and Bank Profitability: Evidence from East Asia - Raz, Arisyi F.; Irawan, Christopher; Indra, Tamarind P.; Darisman, Riki (Journal of Reviews on Global Economics, 2014)
The growing fragility of the financial system has led to the increasing importance of financial supervision’s role. In particular, the financial supervision regime is expected to promote bank performance and maintain financial stability. Unfortunately, studies on the relationship between banking supervisory regimes and bank performance are still limited. To address this issue, this paper focuses on the following four aspects of banking supervision:(i) the structure of supervisory frameworks, (ii) the independence of supervisory institutions (iii) the scope of supervisory role; and (iv) the authority of central banks in the banking sector. We use country-specific data for seven East-Asian countries and data for 39 individual banks in those countries over the period of 2006â€“2011 to examine how different financial supervision regimes in the region influence bank performance. The results show strong evidence that the existence of a single bank supervisor, instead of multiple, will enhance bank profitability. Mean while, there is a mixed result regarding the role of central bank independence in improving bank profitability. Furthermore, the authority of central banks in the banking sector and the scope of bank supervision do not show strong relationship with bank performance.